Anaerobic Bacteria in Biliary Disease in Elderly Patients - Shimada, Kaoru; Inamatsu, Takashi; Yamashiro, Moriya (The Journal of infectious diseases, 1977)
Gallbladder bile from 52 elderly subjects who had undergone biliary tract surgery was examined for the presence of bacteria. Twelve patients had sterile bile, 18 specimens of bile yielded anaerobes as well as aerobes, and 22 yielded aerobic bacteria only. Escherichia coli was the most commonly isolated organism (30 strains). Bacteroides fragilis was the most frequently encountered anaerobic bacterium and was found in 15 patients. The Klebsiella-Enterobacter group was the second most commonly isolated group and B. fragilis was third. Clostridium perfringens was recovered in 10 specimens of bile. Anaerobic bacteria were recovered more frequently in patients with ductal obstruction. The relatively frequent isolation of anaerobes, especially of B. fragilis, in this study may be related to the anaerobic techniques used, to the age of the patients, and to the high incidence of pigment stones among the subjects.